What and how to teach didactics of physics?An approach from disciplinary,sociocultural,and interactiona dimensions - Castiblanco A., Olga L.; Nardi, Roberto [UNESP] (My University, 2018)
The question about what to teach in a physics course apparently has concrete answers depending on phenomena that you want to study such as optics, mechanics, electromagnetism, etc. However, ask about what to teach in a didactics of physics course? It does not seem to have concrete or unified answers. This study aims to propose a structure to work didactics of physics in a teacher education program from three dimensions, based on research results. We developed a phenomenological research design in a qualitative perspective with 14 pre-service physics teachers. We characterized the Didactics of Physics trough disciplinary, sociocultural and interactional dimensions, and consequently, we design and apply a teaching methodology, to analyze the impact and validate this dimensional proposal. Data analysis let us say that take this dimensional perspective to structure objectives, contents, and strategies to decide what and how to teach didactics of physics is highly relevant. We present evidence that pre-service teachers recognized that preparing a physics class requires them to review their capacity of (re)cognition of physics knowledge, their criteria to relate different disciplines to solving physics teaching problems and, understand more broadly different ways to enrich interaction in the classroom. In front of which this proposal contributed importantly to overcome the technical and instrumental vision with is usually assumed teaching didactics.
Keywords: Dimensions of didactics of physics; Initial training teachers; Physics teacher education